Enrichment of Professional Engineering Education - Bhatia, S. C. (Journal of Engineering Education Transformations, 1989)
Due to vast spread of engineering profession and industry, the engineering/technical education has grown rapidly. There is a need to update and enrich the engineering education by incorporation Engineering Management Programmes, Construction Technology&Management, Computer Education, Continuing Education, Refresher Courses, Information and Documentation etc. so that such professional education becomes more and more acceptable to the profession, to the Industry and to the Society.